Quantitative analysis of protein interaction network dynamics in yeast. Issue 7 (13th July 2017) - Celaj, Albi; Schlecht, Ulrich; Smith, Justin D; Xu, Weihong; Suresh, Sundari; Miranda, Molly; Aparicio, Ana Maria; Proctor, Michael; Davis, Ronald W; Roth, Frederick P; St.Onge, Robert P
Abstract: Many cellular functions are mediated by protein–protein interaction networks, which are environment dependent. However, systematic measurement of interactions in diverse environments is required to better understand the relative importance of different mechanisms underlying network dynamics. To investigate environment‐dependent protein complex dynamics, we used a DNA‐barcode‐based multiplexed protein interaction assay in Saccharomyces cerevisiae to measure in vivo abundance of 1, 379 binary protein complexes under 14 environments. Many binary complexes (55%) were environment dependent, especially those involving transmembrane transporters. We observed many concerted changes around highly connected proteins, and overall network dynamics suggested that "concerted" protein‐centered changes are prevalent. Under a diauxic shift in carbon source from glucose to ethanol, a mass‐action‐based model using relative mRNA levels explained an estimated 47% of the observed variance in binary complex abundance and predicted the direction of concerted binary complex changes with 88% accuracy. Thus, we provide a resource of yeast protein interaction measurements across diverse environments and illustrate the value of this resource in revealing mechanisms of network dynamics. Synopsis: A multiplexed assay measures abundance of 1, 379 binary protein complexes in 14 environments. Many environment‐dependent changes were found, enabling exploration of the extent to which network dynamics can be explained by mRNA levels. A DNA‐barcode‐based multiplexed protein interaction assay measured in vivo abundance of 1, 379 binary protein complexes under 14 diverse environments in Saccharomyces cerevisiae . More than half of binary complexes were found to be environment‐dependent, especially those among transmembrane transporters. Many binary complexes changed in a concerted, protein‐centric manner, and under a "diauxic" shift in carbon source from glucose to ethanol, mRNA levels predicted many of the observed changes. Abstract : A multiplexed assay measures abundance of 1, 379 binary protein complexes in 14 environments. Many environment‐dependent changes were found, enabling exploration of the extent to which network dynamics can be explained by mRNA levels.